Maternal and Child Health Inequalities in Ethiopia - Ambel, Alemayehu (Washington, DC, 2016)
Recent surveys show considerable progress in maternal and child health in Ethiopia. The improvement has been in health outcomes and health services coverage. The study examines how different groups have fared in this progress. It tracked 11 health outcome indicators and health interventions related to millennium development goals one, four, and five. These are stunting, underweight, wasting, neonatal mortality, infant mortality, under -five mortality, measles vaccination, and full immunization, modern contraceptive use by currently married women, antenatal care visits, and skilled birth attendance. Trends in rate differences and rate ratios are analyzed. The study also investigates the dynamics of inequalities, using concentration curves for different years. In addition, a decomposition analysis is conducted to identify the role of proximate determinants. The study finds substantial improvements in health outcomes and health services. Although there still exists a considerable gap between the rich and the poor, the study finds some reductions in inequalities of health services. However, some of the improvements in selected health outcomes appear to be pro-rich.